2019
DOI: 10.3892/ol.2019.10238
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic effect of propofol combined with remifentanil or sevoflurane anesthesia on patients undergoing radical gastrectomy

Abstract: Anesthetic effect of propofol combined with remifentanil or sevoflurane intravenous anesthesia on patients undergoing radical gastrectomy was evaluated. The clinical data of 516 cancer patients who received radical gastrectomy in the First Bethune Hospital of Jilin University between January 2011 and December 2017 were retrospectively analyzed. In total 203 patients with propofol combined with remifentanil anesthesia were used as group A, and 313 patients with propofol combined with sevoflurane anesthesia as g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(23 reference statements)
0
3
1
Order By: Relevance
“…These results suggested that compared with propofol alone, sevoflurane combined with propofol can improve the recovery quality from anesthesia, which is consistent with previous reports. 19 Meanwhile, in our study, the HR levels of the two groups immediately after intubation and during exploration were significantly higher than those at the time of entering the room. While the level in the observation group was lower than that of the control group, with statistically significant difference, and there was no significant difference at other time points compared with that at the time of entering the room and the control group.…”
Section: A H E a D O F P R I N Tcontrasting
confidence: 39%
“…These results suggested that compared with propofol alone, sevoflurane combined with propofol can improve the recovery quality from anesthesia, which is consistent with previous reports. 19 Meanwhile, in our study, the HR levels of the two groups immediately after intubation and during exploration were significantly higher than those at the time of entering the room. While the level in the observation group was lower than that of the control group, with statistically significant difference, and there was no significant difference at other time points compared with that at the time of entering the room and the control group.…”
Section: A H E a D O F P R I N Tcontrasting
confidence: 39%
“…It has been frequently reported that propofol can reduce the incidence of emergence agitation in children undergoing sevoflurane anesthesia 18 . The results of Feng et al 19 . showed that patients undergoing radical gastrectomy with the combination of sevoflurane and propofol had stable respiration and circulation during anesthesia, quick recovery of early consciousness and a low incidence of adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…18 It has been frequently reported that propofol can reduce the incidence of emergence agitation in children undergoing sevoflurane anesthesia. 18 The results of Feng et al 19 showed that patients undergoing radical gastrectomy with the combination of sevoflurane and propofol had stable respiration and circulation during anesthesia, quick recovery of early consciousness and a low incidence of adverse reactions. The data presented by Sebel et al 17 showed propofol and sevoflurane to modulate GABA receptor function and generate the anesthetized state in an additive manner, and with good sedation effects.…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic indexes of the two groups at different time points were detected and compared, respectively, before anesthesia, before intubation, 1min after intubation, 1min and 5min after extubation [3] . Visual analogue pain scale was used to evaluate and compare the pain degree at 6h, 12h and 24h after surgery between the two groups [4] .…”
Section: Research Indicatorsmentioning
confidence: 99%